The Enactment of Knowledge Sharing: The Roles of Psychological Availability and Team Psychological Safety Climate - Jing Qian; Wei Zhang; Yi Qu; Bin Wang; Meng Chen (Frontiers in Psychology, 2020)
Scholars have made great efforts to investigate the antecedents of knowledge sharing. In the current study, we applied the proactive motivation model (Parker et al., 2010) to propose a theoretical model to advance this research line and examined the relationship between coaching and knowledge sharing. A total of 197 subordinates embedded in 32 teams from a logistics company completed the survey questionnaire. Our results show that leaders’ coaching behavior is positively related to employees’ knowledge sharing behavior through increased psychological availability. Furthermore, our results show that the team psychological safety climate can strengthen the effect of psychological availability on employees’ knowledge sharing behavior, as well as the indirect effect of leaders’ coaching behavior on employees’ knowledge sharing via psychological availability (i.e., a moderated mediation effect).